A New Achromatic Quarter‐Wave Film Using Liquid‐Crystal Materials for Anti‐Reflection of OLEDs. Issue 1 (June 2014) - Takahashi, Yuta; Furuki, Yusuke; Yoshida, Shinpei; Otani, Taketo; Muto, Masakane; Suga, Yoichi; Ito, Yoji
Abstract We successfully developed a new achromatic quarter wave film for anti‐reflection of OLEDs, consisting of multiple layers of liquid crystal materials. Applying an original optical design, a new liquid crystal compound, and multi‐layer coating technology, we realized OLEDs with very low reflection in all viewing angles. This new film can be produced in a rolled single‐sheet state, which enables the manufacture of a circular polarizer with high productivity by a conventional roll‐to‐roll process.